Sinergi Strategi Komunikasi Public Relations PT Kereta Api Indonesia Daerah Operasi 8 Surabaya dalam Optimalisasi Layanan Digital Access by KAI (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study analyzes the Public Relations communication strategy of PT Kereta Api Indonesia (Persero) Daerah Operasi 8 Surabaya in socializing the Access by KAI digital application to the Surabaya community. Using a descriptive qualitative approach, data were collected through in-depth interviews with PR staff and Railfans Surabaya community members, participatory observation of socialization activities, and documentation of digital publications. Data analysis followed the interactive model of Miles, Huberman, and Saldana (2014). The findings reveal that PR communication strategies are implemented through a synergy of push communication, pull communication, and pass communication, supported by Two-Way Symmetrical Communication principles developed by Grunig and Hunt (1984). Push communication disseminates official information via social media platforms; pull communication attracts audiences through visually compelling and educational content; while pass communication emphasizes two-way engagement that builds public trust and loyalty. The study demonstrates that public engagement, interactive dialogue, and message adaptation to local audience characteristics positively contribute to increasing public understanding and acceptance of the Access by KAI application. The integration of these three strategies creates a holistic communication ecosystem that effectively bridges the gap between digital innovation and user behavior. Future research is recommended to examine similar strategies in other operational regions or employ quantitative approaches to measure adoption levels.